Push-Pull N,N-Diphenylhydrazones bearing bithiophene or thienothiophene spacers as nonlinear optical second harmonic generators and as photosensitizers for nanocrystalline TiO2 Dye-Sensitized solar cells - Fernandes, Sara S. M. (2018)
A series of push-pull heterocyclic N,N-diphenylhydrazones were prepared to study the effect of structural modifications (different pi-spacers and electron withdrawing groups) on the optical (linear and nonlinear) and electronic properties of the molecules.The photovoltaic response of DSSCs assembled using nanocrystalline titania photosensitized with the synthesized dyes was also studied. These heterocyclic push-pull conjugated dyes involve N,N-diphenylhydrazones as electron donors linked to bithiophene or thieno[3,2-b]thiophene spacers, and were functionalized with carboxylic acid, cyanoacetic acid, or dicyanovinyl acceptor groups. A combination of Suzuki-Miyaura cross-coupling, Vilsmeier formylation, and condensation reactions were used to synthesize the intermediates and final products. DFT and TDDFT calculations were used to obtain information on conformation, electronic structure and electron distribution, both for the free dyes and those adsorbed on TiO2. The results of this multidisciplinary study indicate that dyes 5b and 6b have the strongest second order nonlinear optical response with hyperpolarizability values in the range of beta = 2330-2750 × 10-30 esu, while photovoltaic power conversion efficiencies reach values in the range of 0.7-3.0 %, for dyes 5a-b and 7c that were enhanced by co-adsorbing DCA (0.8-5.1 %).